Antiviral therapy (pegylated interferon and ribavirin) of hepatitis C in dialysis patients: meta‐analysis of clinical studies. Issue 10 (16th July 2014) - Fabrizi, F.; Dixit, V.; Messa, P.; Martin, P.
Summary Information on the antiviral treatment (pegylated interferon plus ribavirin) of chronic infection by hepatitis C virus (HCV) in patients on long‐term dialysis is extremely limited. We evaluated the efficacy and safety of combination antiviral therapy (pegylated interferon plus ribavirin) in patients on long‐term dialysis with chronic hepatitis C by performing a systematic review of the literature with a meta‐analysis of clinical studies. The primary outcome was sustained virological response (SVR) (as a measure of efficacy); the secondary outcome was dropout rate (as a measure of tolerability). We used the random‐effects model of DerSimonian and Laird, with heterogeneity and sensitivity analyses. We identified eleven clinical studies (287 unique patients), two of them being controlled clinical trials. The summary estimate for SVR and dropout rate was 0.60 (95% Confidence Intervals, 0.47; 0.71) and 0.18 (95% CI, 0.08; 0.35), respectively; studies being heterogeneous with regard to both the outcomes. Stratified analysis reported a higher SVR rate in controlled trials, 0.86 (95% CI, 0.27; 0.99). The most common sources of dropout were anaemia (11/46 = 23%) and infections (6/46 = 13%). Meta‐regression analysis showed a detrimental impact of HCV genotype 1 (P = 0.036) and dropout (P = 0.0001) rate upon the frequency of SVR. Antiviral therapy based on pegylated interferon plus ribavirin for HCV gives encouraging results in terms of efficacy and safety among patients on long‐term dialysis; such approach should be considered the current standard of care for HCV‐infected individuals on regular dialysis.